The influence of teacher-student relationship on primary school students' moral consensus: a moderated mediation model - Wang, Yao; Chen, Jie; Chang, Huiqing; Li, Guangming (Frontiers in Behavioral Neuroscience, 2026)
ObjectiveThis study aimed to examine the impact of the teacher-student relationship on moral consensus among primary school students, and to investigate the roles of mindfulness, grateful disposition, and social and emotional skills in this relationship.MethodsUsing a cluster sampling method, 2,800 students from grades 3 to 5 across three schools in Guizhou Province completed collective questionnaires offline. Data were analyzed using SPSS 27.0 and the SPSS macro PROCESS to test the hypothesized model. The significance of all regression coefficients was tested using the Bootstrap method.ResultsThe teacher-student relationship significantly and positively predicted moral consensus (c = 0.48, SE = 0.02, p < 0.001). Social and emotional skills and grateful disposition partially mediated the relationship between the teacher-student relationship and moral consensus (a1b1 = 0.12, Boot SE = 0.01; a2b2 = 0.08, Boot SE = 0.01). Mindfulness significantly moderated the first part of the mediation pathway involving the teacher-student relationship and social and emotional skills. As the level of mindfulness increased, the positive predictive effect of the teacher-student relationship on social and emotional skills strengthened (Bsimple at high mindfulness = 0.50, t = 23.74, p < 0.001, increasing from Bsimple = 0.41 at low mindfulness). However, the moderating effect of mindfulness was not significant when grateful disposition served as the mediator.ConclusionsThese findings enhance the understanding of the mechanisms through which the teacher-student relationship influences moral consensus and provide practical implications for fostering moral consensus among primary school students.